2017
DOI: 10.1111/nbu.12244
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of resistant starch

Abstract: The merits of a fibre-rich diet are well documented. Resistant starch (RS) is a form of starch that resists digestion in the small intestine and, as such, is classified as a type of dietary fibre. RS can be categorised as one of five types (RS1-5), some of which occur naturally in foods such as bananas, potatoes, grains and legumes and some of which are produced or modified commercially, and incorporated into food products. This review describes human evidence on the health effects of RS consumption, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
176
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(195 citation statements)
references
References 324 publications
1
176
0
7
Order By: Relevance
“…High GI diets can potentially cause many metabolic syndromes, such as diabetes, obesity and cardiovascular disease (Blaak et al, 2012). Though starch structure, i.e., the morphology and size of starch granules, the ratio of amylose to amylopectin, and the intricate structure of amylose and amylopectin, has an impact on starch digestibility (Lockyer & Nugent, 2017), the indigestible cell wall in the starchy endosperm also plays an important role in its digestibility (Syahariza et al, 2013;Butardo & Sreenivasulu, 2016). In recent years, healthier rice with an improved dietary fibre composition has attracted much attention due to the increasing prevalence of dietrelated non-communicable diseases (Butardo & Sreenivasulu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…High GI diets can potentially cause many metabolic syndromes, such as diabetes, obesity and cardiovascular disease (Blaak et al, 2012). Though starch structure, i.e., the morphology and size of starch granules, the ratio of amylose to amylopectin, and the intricate structure of amylose and amylopectin, has an impact on starch digestibility (Lockyer & Nugent, 2017), the indigestible cell wall in the starchy endosperm also plays an important role in its digestibility (Syahariza et al, 2013;Butardo & Sreenivasulu, 2016). In recent years, healthier rice with an improved dietary fibre composition has attracted much attention due to the increasing prevalence of dietrelated non-communicable diseases (Butardo & Sreenivasulu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These effects have potential relevance to weight loss and weight maintenance and are thought to be due to increased production of SCFAs in the gut which stimulate cells that produce gut hormones. Increased SCFA production has also been described after consumption of the candidate prebiotic, resistant starch (Lockyer & Nugent 2017). Interestingly, a prospective cohort study carried out in Spain (n = 8569 university graduates, mean age 37 years, median follow-up 9 years) reported that risk of overweight was 15% and 17% lower for subjects in the highest quartiles of fructan and GOS consumption, respectively (Perez-Cornago et al 2015).…”
Section: Potential Health Effects Of Prebioticsmentioning
confidence: 99%
“…Starch is a reserve polysaccharide (POLI), commercially isolated from several vegetable sources and when in solution, it presents the following characteristics: high viscosity, easy expansion of granules, and low gelatinization temperature . It is made of two polymers, amylose and amylopectin, whose ratio interferes in its physical, functional, and technological properties …”
Section: Introductionmentioning
confidence: 99%